The estimation trend of Malaysian SME occupational safety and health statistic - Nor Azma Rahlin; Munawar Mustafa; Abdul Halim Abdul Majid (Occupational Health and Safety Society of Nepal, 2018)
The statistic on occupational safety and health has received considerable attention in the SME industry regarding to the vital role of the SME in the Malaysian economy to become a developed country by the year 2020. However, the official statistic specific on SME related occupational safety and health still una-vailable. Thus, the secondary data related to estimation statistic refer to the Department of Statistic (DOS) since 2001 until 2012 were used. Estimation related statistic is adapted from the Global Estimates of Occupational Accidents and Work-related Illnesses 2014. The total number of occupational accident and fatalities average high within ten years. Whereas a number of the accident decrease during 2002 to 2007 with the involvement of 85926 to 56339 cases, nevertheless, four years later trend drastically in-creased. Approximately ten thousand fatal occupational related diseases as 2014. In addition, the cost of compensation claims related occupational accident report increase in 2012 as well as disease and sur-vival recipient. Overall cost of occupational accident increase every year. Presently, this study provided useful hints of implication of ignoring safety to encourage improvement of Occupational Safety and Health (OSH), enhance effectiveness of company operational cost, and stimulate prevention at the SME level substantially great approach to the Malaysian economic development.